SYNERGISTIC EFFECT OF EXTRACTS OF GINKGO BILOBA LEAF AND PANAX GINSENG ROOT ON CARBOHYDRATE AND LIPID METABOLISM GENE EXPRESSION IN ALLOXAN INDUCED DIABETIC RATS - M. Naseem; K. Ouguerram; H. Nazih; I. Rabbani; H. Zaneb; H. U. Rehman; J. Michel; S. K. Tahir (Journal of Animal and Plant Sciences, 2020)
The present study aimed to evaluate the anti-diabetic properties of Ginkgo biloba leaves extract (GBE) and Panax ginseng roots extract (PGE) in different combinations. A total of 40 rats were fed on high-fat-diet for 14-days, then divided into five groups (N=8). Non diabetic group (NDG), Diabetic-group (DG), Mixed-group-1 (MG1), Mixed-group-2 (MG2), Mixed-Group-3 (MG3). Alloxan monohydrate (120-130 mg/Kg BW) was used as a diabetogenic agent. The data of blood glucose and body weight (BW) were monitored regularly weekly. Basal blood was collected from the heart for biochemical analyses. Skeletal muscle, hepatic, and adipose tissue were obtained for mRNA expression of genes. A Significant decrease in BW was found in all treated groups. A significant reduction in fasting serum glucose, AST, ALT, and creatinine were recorded in dose dependent-manner. The treatments showed up-regulation of GLUT-4 in the muscle (all treated groups) and hepatic tissues (MG3); IR in the muscle (MG3) and adipose tissue (MG3), and IRS-1 in hepatic (MG3) and adipose tissue (MG3). Our results showed that these herbs improve dyslipidemia and have strong antioxidant activities. We found significant down-regulation for SREBP-1c in dose-dependent manner in the liver and significant up-regulation for FAS (MG2 & MG3) in the liver. Significant up-regulation was found for PPAR-α in muscles and PPAR-γ in adipose tissues in all treated groups. Significantly down-regulation for TNF-α seemed in all studied organs. In conclusion, GBE and PGE showed strong anti-diabetic, anti-hypercholesterolemia and anti-oxidative effects in combination by regulating the genes involved in carbohydrate and lipids metabolism.
Keywords: Alloxan; Diabetes; Ginkgo biloba leaf extract; Metabolism; Panax ginseng root extract; Rats